Bibliolog: a creative access to the bible - Pohl-Patalong, Uta (W. Kohlhammer, 2015)
'Bibliolog' is an approach to experience the Bible as alive and important for one's own life. A group, congregation or school class discovers biblical stories from within and interprets them by identifying with biblical characters and answering questions left unanswered by the text. Invented by North-American Jewish scholar Peter Pitzele, this approach has its roots in the Jewish tradition of Midrash. It is fascinating how quickly people - whether they have been socialized by the church or not - can be moved by biblical texts when they immediately experience how relevant they still are. Bibliolog has quickly spread across the German-speaking area and is now practiced in many different countries. The growing experience with this approach has led to the decision to offer this concise presentation to an English-speaking audience. Pohl-Patalong focuses on the basic form of Bibliolog, which can be performed in a short period of time and with groups of any size. Prof. Dr. Uta Pohl-Patalong teaches practical theology at the university of Kiel.